ENT 530 Social Media Portfolio: Chan Rak Ter / Muhammad Syukri Mohd Radzi - Mohd Radzi, Muhammad Syukri (2020)
Chan Rak Ter born in Malaysia, raised for the world. Chan Rak Ter is a homegrown brand from Malaysia. We bring milk drinks to life and convenient drinks to life. By revolutionising the milk drinking culture in the region, we strive to be the most loved drink. We bring milk drink which originally came from Thailand to the whole of Malaysia to catch love and addiction to milk drink. Chan Rak Ter has 120 agents at major locations such as Shah Alam, Klang, Petaling Jaya and Damansara at its base in Selangor, Malaysia. The location of the agents will be a major concern, as our targeted audience is young people. This is to ensure that our consumers are easy to meet and that Chan Rak Ter is well known. The company's mission is to ensure that this brand can be more successful in the future. In order to get our loyal customers, we will draw a lot of new potential customers. We also have great hope that one day, Chan Ran Ter will be one of the biggest names in the food and beverage industry to compete with global companies such as Starbuck and Gloria Jeans. To achieve this goal, through the launch of new products and the creation of new distribution channels, Chan Rak Ter will continue to rapidly expand its agents and retail operations, increase its mail order and specialty sales operations, and selectively explore other opportunities to exploit and grow the Chan Rak Ter brand. We will be assisted by our business plan when we become part of the Chan Rak Ter family. Chan Rak Ter is committed to our success, from location selection, construction to organisational, advertisement and marketing support. Through our partnership programme, customised to different levels of expertise and participation, my team will direct from setting up to starting your start-up. As part of our market strategy, Chan Rak Ter also offers cash on delivery (COD) services. One of COD's most valuable advantages as a client is that they can pay only after they have the product in hand. There is no chance of loss of money in that way. We really take care of the feelings of our customers to ensure that they are completely pleased with our product. For example, they don't have to pay directly if they place orders online, instead our nearest agent can COD them and ensure that the product